Hand-Reading: New Pointers for Life Writing - Babs Boter; Alexandra Nagel (European Journal of Life Writing)
The discovery of two handprints of the Dutch journalist and travel writer Mary Pos (1904–1987) and Pos’ reports of her consultations with the Dutch hand-reader in question led to us to reflect on the potential use of such documents in a biographical project aimed at a reconstruction of the life and work of Pos. We first examined the possible reasons for Pos to consult the hand-reader and tried to determine if and how she responded to it in her diaries and correspondence. We also checked whether the hand-reader’s findings had an impact and if she followed his advice. Finally, we wanted to find out if the handprints and reports could perhaps complement the more conventional collection of historical documents already studied, such as Pos’ diaries and letters. We also asked ourselves the more methodological question if a close reading and contextualisation of handprints and their reports in general can contribute to a biographical project. This essay offers a contextualisation of hand-reading practices, a detailed reading of the recovered documents, and a set of considerations when using such sources in a biographical project.